1995
DOI: 10.1002/j.1537-2197.1995.tb11565.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive allocation and the fitness consequences of selfing in two sympatric species ofEpilobium(Onagraceae)with contrasting mating systems

Abstract: Selfing has evolved repeatedly in outcrossing taxa, and theory predicts that an increase in the level of self‐fertilization should occur in concert with changes in reproductive allocation and the magnitude of inbreeding depression. Here we characterize the mating system of two sympatric congeners, Epilobium ciliatum and E. angustifolium, and compare the taxa for 1) reproductive allocation patterns and 2) the fitness consequences of self‐fertilization. For E. ciliatum, autogamy rates were high, pollinator visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 86 publications
2
52
1
Order By: Relevance
“…Given that limited dispersal is common in Macrocystis (Anderson and North 1966, Reed et al 1988, 2004b, the opportunity for self-fertilization should be great. However, while studies on flowering plants show that the costs of selfing frequently decrease with incidence of self-fertilization (Barrett and Charlesworth 1991, Parker et al 1995, Husband and Schemske 1996, they rarely vanish. Moreover, it has been suggested that if the potential for self-fertilization is high and costs are chronically very severe some sort of selfincompatibility will evolve.…”
Section: Discussionmentioning
confidence: 99%
“…Given that limited dispersal is common in Macrocystis (Anderson and North 1966, Reed et al 1988, 2004b, the opportunity for self-fertilization should be great. However, while studies on flowering plants show that the costs of selfing frequently decrease with incidence of self-fertilization (Barrett and Charlesworth 1991, Parker et al 1995, Husband and Schemske 1996, they rarely vanish. Moreover, it has been suggested that if the potential for self-fertilization is high and costs are chronically very severe some sort of selfincompatibility will evolve.…”
Section: Discussionmentioning
confidence: 99%
“…This novel finding supports field genetic data, which indicate extremely localized breeding and strong heterozygote deficiencies in these beds (Rhode, 2002). Chesapeake Bay eelgrass seems to be an exception to this generality, but it resembles other plant populations with limited life spans or restricted windows of reproduction (Parker et al, 1995;Eckert and Schaefer, 1998). Most studies of plants with mixed mating systems have demonstrated that self-fertilization produces fewer seeds and offspring of lower fitness than outbreeding (reviewed in Waser [1993b]).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 11 of 24 maternal parents in the 1987 diallel cross produced both 10-m and 100-m progeny that survived to flower, thus yielding estimates of for both crossing distance treatments applied to each parent. Based on this measure the variation among maternal sibships is impressive, ranging from outbreeding depression of 40% to Ϫ14% (calculated as {[ 10m Ϫ 100m ]/ max [ 10m , 100m ]}, which yields a symmetrical measure bounded by ϩ1 and Ϫ1, with negative values indicating heterosis at the longer relative to the shorter distance; see Parker et al 1995;Dudash et al 1997). In 1990 we used 36 plants as parents, but each was used in fewer matings, and we obtained comparable information for only seven maternal parents; here the range in outbreeding depression was 31% to Ϫ57%.…”
Section: Discussionmentioning
confidence: 99%
“…Their table 2 indicates substantial variation in germination of seeds resulting from crosses among blueberry varieties, ranging from outbreeding depression of 68% to Ϫ38%. Turning to the level of individual plants, Parker et al (1995) applied pollination treatments of selfing and ''outcrossing'' (i.e., nonself crosses within populations) in two species of Epilobium and assessed the short-term performance of progeny in the greenhouse. Performance varied among maternal sibships, with outbreeding depression ranging in E. ciliatum from 40% to Ϫ20% and in E. angustifolium from 80% to Ϫ100%.…”
Section: Discussionmentioning
confidence: 99%